Dental caries and periodontal diseases in Mozambique (Research, Society and Development, 2022)
Objective: To determine the rate of dental caries and periodontal rates in Mozambican population. Material and Methods: The sample size was 722, categorized in age groups of 6,12, 15-19 and 35-44 in public schools and markets randomly selected in five provinces of Mozambique (Maputo, Gaza, Manica, Tete and Zambezia), in urban and rural areas. Clinical examinations were performed by calibrated examiners using WHO, DMFT/dmft and CPI indexes. Data analysis was descriptive and analytical, using a Chi-square test and Pearson's correlation (P